Identification of Fragrance-Related Transcripts from Selected Orchids Using cDNA Representational Difference Analysis (cDNA-RDA) Approach - Barudin, Mohd Aiman; Mohd Hairul, Ab. Rahim; Tan, Suat Hian (International Journal of Interdisciplinary and Multidisciplinary Studies, 2015)
Volatile components have been identified in hundreds of orchids including species and hybrids, but the biochemical and molecular biological knowledge on the biosynthesis of scent compounds in orchids is still limited. To date, a strategy combining chemical analysis, genomics and bioinformatics is adopted to unravel the scent biosynthetic pathways that are involved in floral scent biosynthesis in orchids. In this study, cDNA-RDA was used to identify fragrance-related transcripts in three selected fragrant-orchids includingVanda Mimi Palmer, Vanda Small Boy Leong and Vandachostylis Sri-Siamin comparison to Vanda Tan Chay Yan, a nonfragrant orchid. This cDNA-RDA approach allows us toisolate cDNA fragments that are presentin selected fragrant orchids but absent in non-fragrant orchid. Double-stranded cDNA of each fragrant orchid was hybridized separately with double-stranded cDNA of the selected non-fragrant orchid and followed by amplification of subtracted fragments. Three rounds of cDNA-RDAwere carried out to enrich difference cDNA fragments.A number of 21 clones of difference products were sequenced and sequence analysis has shown the presence of three different putative fragrance-related transcripts including methionine synthase, S-adenosyl-Lmethionine synthase, and phenylalanine ammonia lyase. All of the identified transcripts might be involved in fragrance biosynthesis of those fragrant orchids